The Existence of Rumah Gadang in Kuok Village West Bangkinang District Kampar Regency - Dhari, Belirda Wulan; Ermansyah, Ermansyah; Susmiarti, Susmiarti (Gondang: Jurnal Seni dan Budaya, 2023)
Rumah Gadang as a characteristic of the Minangkabau ethnic group within the government of Povinsi Riau. Nowadays Rumah Gadang in Kuok regency of Kampar regency is abandoned by its owner and neglected to make its condition worrisome. Cultural place of residence, RumahGadang is a place of cultural social activities of Ethnic Minang in Kanagarian Kuok Kampar regency. In fact, Rumah Gadang is no longer functioned by the Kuok community in its role in Minangkabau adat. This paper highlights the existence of the current Gadang House in the socio-cultural life of the Kuok people. This research was conducted with qualitative research approach, with descriptive method. The data were collected by observation, interview, documentation and through bibliography. The research instrument is the researcher himself as a key instrument. From the results of research and data analysis that the existence of the Rumah Gadang (Lontiok House) is not fully intact, even some of it has been damaged and lost because in addition to changing times that are constantly changing, the condition of the area that is not supportive, and also because of the mobile community. Thus the status of Riau Province, especially Kampar Regency which was formerly a part of Minangkabau (West Sumatera) is not the influence of cultural objects (Rumah Lontiok) abandoned, changed, but because of socio-cultural change factors consisting of internal factors including factors family, economy, condition of building materials, new innovations, especially in the building system of the house